Academic Information System at SD Negeri 1 Sidomakmur Using the Web Engineering Method - Imam Hasyah Frans (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2023)
The management of students, teachers, and learning activities at SD Negeri 1 Sidomakmur has been partially computerized. However, the school continues to rely on basic applications such as Microsoft Word and Excel for administrative tasks. Considering the rapid advancement of digital technology, it is essential for SD Negeri 1 Sidomakmur to implement a specialized web-based information system to support administrative and academic operations more efficiently. The proposed system enables seamless data processing and integration across all school activities, thereby facilitating faster and more accurate management of teaching and learning processes. This study aims to develop a web-based academic information system utilizing the Web Engineering method, the PHP programming language, and the MySQL database. The implementation of this system is expected to enhance the effectiveness, accuracy, and reliability of the school’s administrative and academic management.